Textual selection and progression in teaching the basics of legal translation - Le Poder, Marie Evelyne (Íkala, Revista de Lenguaje y Cultura, 2007)
This work is about text selection and progression in teaching introductory legal translation, that is to say, about the initiation phase of this specialization. Textual selection and progression constitute the Achilles heel of translation didactics since establishing real applicable valid criteria for textual selection from a didactic point of view is a diffi cult task. The methodological proposal I offer is based on the subjects of Economics, Commerce and Legal Translation, part of the four-year undergraduate Translation Studies at the University of Granada, as well as the rest of Translation Studies in Spain. Recibido: 21-03-07 / Aceptado: 30-07-07 How to reference this article: Le Poder, M.-E. (2007). Selección textual y progresión en la enseñanza introductoria a la traducción jurídica. Íkala. 12(1), pp. 11 – 23.